Stablecoin assessment framework - Alejandro García; Bena Lands; Dennis Yanchus (Bank of Canada, 2021)
We outline a three-step framework to investigate stablecoin arrangements and quantitatively assess their risk. The first step is to classify the stablecoin arrangement into three parts-coin structure, transfer system(s) and financial service(s) - and categorize the attributes of each part. The second step is to identify specific risk scenarios. The third is to quantify the range of probable loss and range of possible frequency associated with the identified risk scenarios. Our proposed framework allows authorities to understand the defining characteristics of stablecoin arrangements, to be specific about any concerns they may have, and to be objective in their treatment from issuer to issuer. Additionally, the process we are proposing ensures that authorities and the stablecoin issuer can come to a quantitatively based understanding about the potential risks. The main contributions we make are to separate stablecoins arrangements into three activity-based components and to apply an operational risk management approach to quantifying risks of stablecoins.
Keywords: D78; D81; G01; G18; O3; O38; 330; Digital currencies and fintech; financial institutions; Financial system regulation and policies; Financial markets; Payment clearing and settlement systems